Profile of intimate partner violence in Family Health Units - Ricardo de Mattos Russo Rafael; Anna Tereza Miranda Soares de Moura; Jeane Marques Cunha Tavares; Renata Evelin Moreno Ferreira; Glauce Gomes da Silva Camilo; Mercedes Neto
ABSTRACT Objective: To estimate the profile of intimate partner violence involving women in a scenario of Family Health Strategy in the municipality of Nova Iguaçu (Rio de Janeiro). Method: A transversal study was conducted in four units with a sample of 640 women between the ages of 25 to 64. The phenomena of violence was determined using the tool Revised Conflict Tactics Scales, validated for Brazil. Statistical analysis took into consideration an estimation of prevalence in the calculation of the p values. Results: The situations of violence and the sociodemographic profiles demonstrated a statistically significant relationship with the variables of educational level and housing conditions. Age, ethnicity and economic class demonstrated an association with certain types of violence, varying in type and severity. Conclusion: The study investigated the profile of these situations of violence and enabled reflection regarding the approaches adopted by the Family Health Strategy teams.